Posisi Politik Komisi Pemberantasan Korupsi Analisis Pemangku Kepentingan Pada Organisasi Publik - Suwarsono, Suwarsono (Program Magister Manajemen STIE Widya Wiwaha Yogyakarta, 2016)
This paper attempts to find the political position of Komisi Pemberantasan Korupsi (The Corruption Eradication Commission) in the year of 2014. In so doing, it tries to use the stakeholders perspective as its theoretical framework which applied in public sector context. Stakeholders analysis is basically a political dimension of management. First, it shortly expouses what is meant by the stakeholders perspective. It is followed by an explanation about its mode of analysis and its strategic implication. Core of the paper is found where it explains the political position of Komisi Pemberantasan Korupsi (KPK) in its final part which includes a set of proposed strategy. Key words: public sector, stakeholders, political position, and proposed strategy